Final answer:
To solve the system of equations, we simplified and solved to find that x = 1 and y = 1. The required value of xy is therefore 1.
Step-by-step explanation:
The student provided two equations which form a system:
y = x^2
2y + 6 = 2(x + 3)
To find the solution to this system, we first simplify the second equation:
2y + 6 = 2x + 6
By simplifying, we get:
y = x
Since we have y = x and also y = x^2 from the first equation, we can equate them as they both equal to y:
x = x^2
Now solve for x, knowing that x > 0:
x^2 - x = 0
x(x - 1) = 0
This gives us two solutions for x: x = 0 or x = 1, but since x > 0, the valid solution here is x = 1.
Substituting x = 1 into y = x^2 gives us y = 1^2 = 1.
Therefore, we have solved for both x and y, and the point is (1,1).
Finally, to find the value of xy, we multiply x and y together:
xy = 1 * 1 = 1